2016
DOI: 10.1213/ane.0000000000001099
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in Grading Methods of Aortic Stenosis by Pre-Cardiopulmonary Bypass Transesophageal Echocardiography

Abstract: Discordance in Grading Aortic Stenosis by Pre-CPB TEE aortic valve. For this reason, AVA calculation is prone to error compared with a ΔP m measurement.Although inconsistencies for grading AS with AVA and ΔP m are well known for preoperative TTE, they are routinely used for grading AS in the pre-cardiopulmonary bypass (pre-CPB) context. In this study, we investigate the frequency of discordance between grading AS with ΔP m measurements and AVA calculations during pre-CPB transesophageal echocardiography (TEE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…5 Additional research has shown that there is more discordance between mean PG m and AVA during precardiopulmonary bypass TEE than during preoperative TTE. 6 In a perfect world, one could perform a TEE examination and have certain parameters be in complete agreement with previously reported studies across all modalities. However, we know this not to be uniformly true.…”
supporting
confidence: 83%
“…5 Additional research has shown that there is more discordance between mean PG m and AVA during precardiopulmonary bypass TEE than during preoperative TTE. 6 In a perfect world, one could perform a TEE examination and have certain parameters be in complete agreement with previously reported studies across all modalities. However, we know this not to be uniformly true.…”
supporting
confidence: 83%
“…What is classified as 'mild' during surgery might in fact be at least 'moderate' in severity if the valve was examined in an awake patient, without the influences of general anaesthesia and positive pressure ventilation. 10 Expectant management is considered appropriate in mild AS because of increased mortality and morbidity in AVR combined with coronary bypass grafting compared with isolated coronary bypass grafting alone. 1 However, the current American and European guidelines suggest that AVR is reasonable or should be considered in patients with moderate AS undergoing cardiac surgery for other indications.…”
Section: Discussionmentioning
confidence: 99%
“…2 11 A recent retrospective analysis concluded that grading of AS by aortic valve area and mean pressure gradient showed higher discordance in intraoperative TOE compared with preoperative TTE. 10 Although a reduction in mean gradients under general anaesthesia was suggested to be one of the causative factors, this was not specifically evaluated. We are unaware of any previous studies that have evaluated how the echocardiographic assessment of AS severity changes in the intraoperative setting.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Discrepancies are frequently observed in grading severity of AS using above parameters between transthoracic and TEE imaging. [6] In a retrospective, observational study preoperative TTE PGm and AVA values were compared with precardiopulmonary bypass (CPB) TEE, and it was found that preCPB TEE often underestimates AS severity. [7] The reason for this disparity is unclear.…”
Section: Introductionmentioning
confidence: 99%